ANALISIS SISTEM DAN PROSEDUR PEMUNGUTAN PAJAK BUMI DAN BANGUNAN (PBB) PADA BADAN KEUANGAN DAERAH KABUPATEN KAPUAS HULU - B1032131032, HEVY WAHYULI (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
The purpose of this research is to know the system and procedure of collecting of land and building tax which is executed by Regional Finance Board of Kapuas Hulu Regency and to know the level of effectivity from collecting and receiving tax of earth and building to original income of Kapuas Hulu regency. In this research the research used descriptive method using qualitative approach. Data collection techniques using Interviews, Questionnaires and Library Studies. From the results of the study concluded that the system and procedure of collecting land and building tax conducted by Regional Finance Agency of Kapuas Hulu Regency in accordance with Local Regulation No. 8 of 2011 About Local Taxes and Regional Regulation No. 5 of 2014 About Procedures for Collection of Land and Building Tax and Control Internally implemented is good enough. And based on the calculation of the effectiveness of tax revenues of land and building from 2014-2016 is effective even though still not reached the target set. Where in 2014 the realization of revenue is 89.29%, in 2015 revenue realization that is equal to 85.13% and in 2016 revenue realization that is equal to 87.73%. By looking at the percentage of non-permanent realization, there is still a weakness of internal control within the Regional Finance Board, so there is a need for further improvements in the internal control system that has not gone well with the Regional Finance Agency. Keywords: Internal Control System, Land and Building Tax.